Successful repair of thoracic wall defect using an ovine rumen BioGraft in a dog - Raidurg, Ravi; Dhoolappa, M.; Lakshmishree, K.T.; Malatesh, D.S.; Kiran Shankar, H. (Indian Journal of Veterinary Surgery, 2026)
-